Mapping lineage-traced cells across time points with moslin - Marius Lange; Zoe Piran; Michal Klein; Bastiaan Spanjaard; Dominik Klein; Jan Philipp Junker; Fabian J. Theis; Mor Nitzan (Genome Biology)
Abstract Simultaneous profiling of single-cell gene expression and lineage history holds enormous potential for studying cellular decision-making. Recent computational approaches combine both modalities into cellular trajectories; however, they cannot make use of all available lineage information in destructive time-series experiments. Here, we present moslin, a Gromov-Wasserstein-based model to couple cellular profiles across time points based on lineage and gene expression information. We validate our approach in simulations and demonstrate on Caenorhabditis elegans embryonic development how moslin predicts fate probabilities and putative decision driver genes. Finally, we use moslin to delineate lineage relationships among transiently activated fibroblast states during zebrafish heart regeneration.